Ginkgo biloba L.: An Updated Review on the Pharmacological Activities, Pharmacokinetics and Drug Interactions - Zahra Moeinipour; Maryam Akaberi; Zahra Sobhani (Traditional and Integrative Medicine)
Medicinal herbs have recently received considerable public attention for their therapeutic properties. Traditional healing systems such as Ayurveda, traditional Chinese medicine, and traditional Persian medicine highly rely on medicinal plants to treat many diseases. However, herbal medicines are usually not standardized and despite their widespread use, there is limited scientific evidence on their safety and interactions. Ginkgo biloba L. is a medicinal plant whose biological properties have been confirmed in previous studies. Its leaf extract exhibited anti-inflammatory, antioxidant, neuroprotective, and anti-apoptotic properties. Nevertheless, G. biloba contains various pharmacologically active components, such as terpene lactones and flavonoids that could cause drug interactions through multiple mechanisms, including the effect on cytochrome isozymes and p-glycoprotein (P-gp). Thus, conducting studies to evaluate this plant's safety profile and drug interactions seems necessary. In the current paper, we reviewed the pharmacokinetics, drug interactions, and pharmacological properties of G. biloba plant. According to the included studies, bioactive compounds found in G. biloba extract have antagonistic activity against platelet aggregation and could inhibit human thrombin, thereby increasing the risk of severe bleeding. We also identified several other potential drug interactions for G. biloba, including risperidone, thiazides, mycophenolic acid, and diltiazem. Data on drug interactions between G. biloba and digoxin, simvastatin, nicardipine, and midazolam were less consistent. Therefore, caution should be taken in consuming this plant with anticoagulants or platelet inhibitors such as warfarin, ticlopidine, clopidogrel, and aspirin. However, patients’ age, gender, and dosage forms of medicine seem to play an essential role in drug interactions. In summary, further clinical and laboratory research is necessary to elucidate the risk of G. biloba drug interactions. Also, the use of technologies such as genomics, metabolomics, and transcriptomics can provide a more comprehensive understanding of how G. biloba interacts with drugs at the molecular level.